Pre-Hospital Care and Referral Pattern among Admitted Patients with Dengue Fever in Dhaka Medical College Hospital (Journal of Medicine, 2025)
Introduction: Dengue has become a pressing public health concern for Bangladesh, with a significant rise in the death toll in recent years. Dhaka Medical College Hospital, the largest referral hospital, treats a large number of patients dengue patients. This study aims to observe prehospital treatment and referral patterns among patients admitted to the hospital with dengue fever.Methods: This observational, cross-sectional study was conducted at Dhaka Medical College Hospital from September 2023 to November 2023, involving patients admitted with dengue infection. All consecutive patients with laboratory-confirmed dengue admitted to one unit (Medicine unit: 3) of the Department of Medicine were included. The data were analyzed using SPSS 25 software.Results: Among the 488 patients, 273 (55.9%) were male. Most patients range in the age group 26-44 (39.5%). The Mean age of patients was 34.16±16.06. The majority, 160 (32.8%) and 123 (25.2%) were homemakers and students, respectively. Most patients (50%, n=244) were diagnosed with Dengue with warning signs (Category B). The mean hospital stay duration was 5.05±2.018 days, and the majority, 438 (89.8%), stayed in the hospital for ≤7 days. The mean ± SD of illness duration was 5.58 ±2.32 days. About 125 (25.6%) patients had co-morbid diseases, and hypertension was the most frequent comorbid condition. The majority of patients, 436 (89.3%) had no co-infections. Eighty-one (16.6%) and 79 (16.2%) patients were treated with antibiotics and papaya leaf extract juice or capsule before hospital admission, respectively, and a few patients used Eltrombopag (2.9%) as well. Among 488 patients, 201 (41.2%) patients were admitted by themselves. Approximately 479 (98.2%) patients survived and were discharged, and five patients died, all of them admitted to the hospital with severe dengue (Category C).Conclusion: A significant portion of patients had practices using medication like antibiotics, steroids, papaya eltrombopag, etc., without indication of use. Self-hospitalisation without using a referral system was the most common form of hospitalization among patients with dengue fever.J MEDICINE 2025; 26: 36-42